The mechanical properties of natural materials. II. Microstructures for mechanical efficiency - Karam, G.N. (1995)
Many natural materials have exceptionally high values of the mechanical performance indices described in the previous, companion paper. For beams and plates of a given stiffness or strength, or for a column of a given buckling resistance, woods, palms and bamboo are among the most efficient materials available. Their mechanical efficiency arises from their combination of composite and cellular microstructures. In this paper we analyse the microstructures which give rise to exceptional performance, describe the fabrication and testing of model materials with those microstructures and discuss the implications for design of mechanically efficient engineering materials.